THE IMPACT OF FINANCIAL RISKS ON BANK PERFORMANCE IN INDONESIA COMMERCIAL BANKS - Jihan Annasyha; Ghinaa Amadea Hanindityasari; Susy Muchtar (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study examines how financial risks affect the performance of banks listed on the Indonesia Stock Exchange, with return on equity (ROE) as the primary profitability metric. The study, covering the period 2020 to 2024, employs a regression model to ensure a robust and comprehensive analysis. The data includes audited annual financial statements from selected banks. Macroeconomic indicators, such as GDP growth and inflation, are sourced from the Central Bank of Indonesia (BI) and the World Bank (WB). This study explores critical financial risks affecting bank performance, focusing on credit, liquidity, and operational risks. The study also considers the impact of bank size, GDP growth, and inflation rates on bank performance. The analysis reveals a clear negative impact of these financial risks on bank performance: higher liquidity and operational risks are associated with lower financial performance. At the same time, bank size also positively impacts performance, as larger banks are associated with improved financial performance. This underscores the importance of financial risk management in effectively monitoring and controlling key performance indicators in consolidated commercial banks. Furthermore, both macroeconomic conditions and bank-specific attributes are shown to influence financial results significantly. By offering an in-depth perspective on risk management strategies, this study provides practical recommendations to enhance financial stability and strengthen the resilience of commercial banks in Indonesia in the evolving economic landscape.